Pola Hubungan Petani Penggarap dengan Pihak Pengelola Taman Nasional Kelimutu dalam Pengelolaan Lahan Desa Penyangga Kawasan Taman Nasional Kelimutu (Studi Kasus: Desa Pemo Kecamatan Kelimutu Kabupaten Ende) - Florentina Nadina Lengo; Maria M. E. Purnama; Astin E. Mau; Wilhelmina Seran (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2026)
Pemo Village is one of the buffer villages of the Kelimutu National Park area, where most of the people earn a living as farmers. The Kelimutu National Park management has a community empowerment program for buffer villages, including Pemo village. Pemo village farmers who in land management still apply the slash and burn system and shifting cultivation cause a lot of idle land in Pemo village and can have a negative impact on the environment. Community-owned land has the potential to be developed so that the community empowerment provided can help in utilizing the land properly, so this study aims to find out how the relationship between Pemo village farmers and the Kelimutu National Park management in land management. Respondents in this study were farmer groups in Pemo village using purposive sampling technique. Data collection techniques include interviews, observation, documentation and analyzed descriptively qualitative. The results showed that the relationship between the Kelimutu National Park and farmers in land management in Pemo village is a good and positive relationship in the form of community empowerment and cooperation with one of the groups, namely the Nira Ika group. The provision of seedlings, saplings, and apple orchard agro-tourism has a good purpose for the community in utilizing the existing land. Community empowerment also aims to increase community income and as an effort to preserve the Kelimutu National Park area.